La fonte de la biodiversité dans les îles : modélisation de l’impact du réchauffement global sur la végétation orophile de Tahiti (Polynésie française) - Robin Pouteau (Éditions en environnement VertigO, 2010)
Between 60 and 70 % of the native flora of the islands of French Polynesia (South Pacific) are located in montane ecosystems, in the so-called “orophilous vegetation“. Due to its cooler climate, this high elevation zone is relatively protected from anthropogenic activities and from the invasion of alien species which are particularly aggressive at lower elevations. If global warming, recorded to be 0.034°C per year since 1958 in the main island of Tahiti, is persisting, air temperature will increase by 3.1°C in 2100, causing a vertical shift of vegetation and a drastic decrease of the orophilous vegetation area. Some endemic species unable to migrate higher in elevation will be doomed. According to our results, orophilous vegetation will decrease from 14,000 ha nowadays to 1,500 ha in 2100, which represents a 90 % reduction of the current area. Consequences on biodiversity will be : (i) the loss of a unique ecosystem in French Polynesia, the subalpine zone, and the extinction of, at least, six plant species restricted to this habitat and endemic to Tahiti ; (ii) the loss and fragmentation of the cloud forests, which will only be found on the highest summits, leading to an additional risk of extinction ; and (iii) the expansion of alien invasive species, having already an enormous ecological impact in Tahiti.